2010
DOI: 10.1038/ejcn.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

The study to investigate the potential benefits of probiotics in yogurt, a patient-oriented, double-blind, cluster-randomised, placebo-controlled, clinical trial

Abstract: Background: Probiotic functional foods are widely advertised to consumers primarily based on probiotic supplements. Objective: Determine if consumption of yogurt containing a high dose of probiotics improves health in children ages 1-3 years attending daycare/school centers. Subjects/Methods: Double-blinded, randomized, placebo-controlled, allocation concealment clinical trial. Setting: Outpatient participants in the Washington, DC area. Participants: 182 healthy children between the age of 1 and 3 years atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…In contrast to gastrointestinal infections, all studies in children older than one year of age who attend day care centers found that probiotics significantly lowered the incidence of upper respiratory tract infections [5,6,9,15,16]. Moreover, in 2011 the Cochrane metaanalysis identified 10 trials which involved 3451 participants, not limited only to children [11].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to gastrointestinal infections, all studies in children older than one year of age who attend day care centers found that probiotics significantly lowered the incidence of upper respiratory tract infections [5,6,9,15,16]. Moreover, in 2011 the Cochrane metaanalysis identified 10 trials which involved 3451 participants, not limited only to children [11].…”
Section: Discussionmentioning
confidence: 91%
“…as a single strain in seven RCTs [13,16,17,[20][21][22]24], strains of Bifidobacterium spp. in four RCTs [11,12,14,15] and different combinations of Lactobacillus and Bifidobacterium strains in three RCTs [18,19,23]. The duration of probiotic treatment varied between 3 and 12 months.…”
Section: Probiotic Treatmentmentioning
confidence: 99%
“…Of the total 14 RCTs, 13 involved healthy children or infants [11][12][13][14][15][16][18][19][20][21][22][23][24] and 1 involved hospitalized children [17]. Eight of the 14 included RCTs studied specific populations of children attending daycare.…”
Section: Characteristics Of the Studied Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of one product cannot be transferred to another. In a study recently conducted by the same working group [28] and following a similar study design, the strain B . animalis ssp.…”
mentioning
confidence: 99%